Work Environment and Health Conditions of Elementary School Teachers During The Covid-19 Pandemic - Imas Soemaryani; Wa Ode Zusnita Muizu; Dara Sagita Triski (Jurnal Manajemen Universitas Bung Hatta, 2023)
Work environment change during the Covid-19 pandemic caused symptoms of health problems. Since the online school, teachers at the Nurul Islam Integrated Islamic Elementary School, Cahaya Ilmu Elementary School, and Al-Iman Elementary School have experienced mental and physical health problems. Mental health disorders such as work stress, both stress that comes from within themselves and from the organization/environment. Physical health problems felt by the teachers were eye nerve disorders, joint disorders, muscle and spinal disorders. The purpose of this study was to analyze the impact of the work environment on the health conditions, especially for the mental and physical health of teachers, the sample in this study is 138 people. The data collection techniques used surveys, interviews, and distributing the questionnaires, and the data processing and analysis techniques used simple linear regression methods.  The results of the partial analysis there is a negative amount of 20,6% influence between the work environment on healthy conditions, this means that any unfavorable high state of the work environment will deteriorate the teacher's physical and mental health.